Đáp án: [TEX]A_{min} =\frac{2}{3}[/TEX] \Leftrightarrow [TEX]x =1[/TEX]
Ta có: [TEX]A =\frac{x^2+2x+3}{(x+2)^2}[/TEX]
\Leftrightarrow [TEX]A.(x+2)^2 =x^2 +2x +3[/TEX]
\Leftrightarrow [TEX]A.x^2 +4Ax +4A -x^2 -2x -3 =0[/TEX]
\Leftrightarrow [TEX](A-1).x^2 +(4A -2)x +(4A -3) =0[/TEX] (1)
Đặt A-1 =a; 4A -2 =b và 4A-3 =c, thay vào công thức Delta, ta có:
[TEX]\Delta =b^2 -4ac[/TEX]\geq0 \Leftrightarrow[TEX](4A -2)^2 -4(A-1)(4A-3)[/TEX] \geq0
\Leftrightarrow [TEX]16A^2 -16A +4 -16A^2 +28A -12[/TEX]\geq0
\Leftrightarrow [TEX]12A -8 [/TEX]\geq0 hay A\geq [TEX]\frac{2}{3}[/TEX]
Do vậy, [TEX]A_{min} =\frac{2}{3}[/TEX]. Dấu "=" xảy ra \Leftrightarrow
[TEX]\frac{-1}{3}x^2 +\frac{2}{3}x -\frac{1}{3} =0[/TEX] (Thay [TEX]A =\frac{2}{3}[/TEX] vào (1) thì ta có như vậy)
\Leftrightarrow [TEX]\frac{-1}{3} x^2 +\frac{1}{3}x +\frac{1}{3}x -\frac{1}{3} =0[/TEX]
\Leftrightarrow [TEX](\frac{-1}{3}x +\frac{1}{3})(x -1) =0[/TEX]
\Rightarrow x = 1
Vậy: [TEX]A_{min} =\frac{2}{3}[/TEX] \Leftrightarrow[TEX]x =1[/TEX]